Analisis Validitas dan Praktikalitas dari Modul Minyak Bumi Berbasis Guided Discovery Learning - Winda Permatasari; Yerimadesi Yerimadesi (Edukimia, 2020)
The purpose of development research is to produce and analyse the validity and practicality of the guided discovery learning based on petroleum module for class XI SMA/MA. This research uses the Plomp development model. The validity test was conducted on 4 chemistry lecturers and 2 chemistry teachers. The practicality test was carried out by 2 chemists and 30 students of class XII SMA in 2019/2020. The research instrument used was a questionnaire of validity and practicality. The data obtained were analysed with Cohen’s kappa formula. From the result of study obtained an average value of kappa moments of module validity (0,89), module practicality by teachers (0,93) and module practicality by students (0,83). The data shows that the module is valid and practical for learning chemistry.